Bubulcus ibis (cattle egret) conservation with awig-awig (customary law) in Bali, Indonesia - FX Sudaryanto; JUNITA HARDINI; LALU ACHMAD TAN TILAR WANGSAJATI SUKMARING KALIH; I WAYAN SUANA (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sudaryanto FX, Hardini J, Kalih LATTWS, Suana IWS. 2022. Bubulcus ibis (cattle egret) conservation with awig-awig (customary law) in Bali, Indonesia. Biodiversitas 23: 1904-1910. The study on the conservation of Bubulcus ibis (Linnaeus, 1758) in Petulu Village, Ubud, Bali, Indonesia, was conducted to determine the population dynamics and behavior of B. ibis the vegetation used, the conservation efforts by the community, and the benefits to ecotourism. The population of B. ibis in August 2019 was 625 ± 12 birds, 7053 ± 15 birds in February 2020, and 465 ± 17 birds in July 2020. In Petulu Village, B. ibis breeds from December 2019 to February 2020. The most commonly used tree for nesting was Ficus subcordata Bl. Based on in-depth interviews, 100% of the inhabitants of Petulu Village were willing and carried out the conservation of B. ibis with awig-awig. The tourists who come to Petulu are 100% amazed by the use of awig-awig (traditional law) as the B. ibis conservation method.